PHYSICAL THERAPY PROGRAM IN THE TREATMENT OF MYOCARDIAL INFARCTION AT THE INPATIENT STAGE - Borovets, O. V.; Romanova, V. I.; Sirman, O. V. (Rehabilitation and Recreation, 2021)
Relevance. Sad statistics show that 68% of deaths in Ukraine are the result of cardiovascular disease (CVD). Therefore, it is absolutely fair to say that every second death in our country – from cardiovascular disease. Physical therapy of MI patients acquires important socio-economic significance. Solving the problem and preventing complications as a result of acute MI, improving the quality of life of this category of patients require the search for new scientifically sound, safe and affordable rehabilitation programs and methods for evaluating their effectiveness. Materials and methods of research. The study, with the consent of patients, involved 50 patients who were in the recovery phase after acute myocardial infarction and completed a full course of inpatient treatment. Statistical analysis was performed using the statistical analysis program Medstat [6]. The methodology of building the author’s program of physical therapy provided strict dosing and gradual increase of physical activity in volume and intensity, number and complexity of exercises, taking into account clinical features of the underlying disease and comorbidities, age of patients, analysis of laboratory and instrumental data, functional methods. Results of the study – After the study and the use of the developed means of physical rehabilitation observed improvement in the most pronounced in the group of patients with small focal MI, after the use of physical rehabilitation – 7.7%, p <0.05. In the group of patients with focal MI after physical rehabilitation and appropriate medical treatment – 36.0%, p <0,01. The effectiveness of the use of the developed author’s program of physical therapy after MI is confirmed by the data of positive dynamics. Conclusions. According to the results of our study, the effectiveness of individual classes and integrated use of physical therapy was proved.